Oxidative stress, metabolomics profiling, and mechanism of local anesthetic induced cell death in yeast - Cory H.T. Boone; Ryan A. Grove; Dana Adamcova; Javier Seravalli; Jiri Adamec (Redox Biology, 2017)
The World Health Organization designates lidocaine as an essential medicine in healthcare, greatly increasing the probability of human exposure. Its use has been associated with ROS generation and neurotoxicity. Physiological and metabolomic alterations, and genetics leading to the clinically observed adverse effects have not been temporally characterized. To study alterations that may lead to these undesirable effects, Saccharomyces cerevisiae grown on aerobic carbon sources to stationary phase was assessed over 6 h. Exposure of an LC50 dose of lidocaine, increased mitochondrial depolarization and ROS/RNS generation assessed using JC-1, ROS/RNS specific probes, and FACS. Intracellular calcium also increased, assessed by ICP-MS. Measurement of the relative ATP and ADP concentrations indicates an initial 3-fold depletion of ATP suggesting an alteration in the ATP:ADP ratio. At the 6 h time point the lidocaine exposed population contained ATP concentrations roughly 85% that of the negative control suggesting the surviving population adapted its metabolic pathways to, at least partially restore cellular bioenergetics. Metabolite analysis indicates an increase of intermediates in the pentose phosphate pathway, the preparatory phase of glycolysis, and NADPH. Oxidative stress produced by lidocaine exposure targets aconitase decreasing its activity with an observed decrease in isocitrate and an increase citrate. Similarly, increases in α-ketoglutarate, malate, and oxaloacetate imply activation of anaplerotic reactions. Antioxidant molecule glutathione and its precursor amino acids, cysteine and glutamate were greatly increased at later time points. Phosphatidylserine externalization suggestive of early phase apoptosis was also observed. Genetic studies using metacaspase null strains showed resistance to lidocaine induced cell death. These data suggest lidocaine induces perpetual mitochondrial depolarization, ROS/RNS generation along with increased glutathione to combat the oxidative cellular environment, glycolytic to PPP cycling of carbon generating NADPH, obstruction of carbon flow through the TCA cycle, decreased ATP generation, and metacaspase dependent apoptotic cell death. Keywords: Local anesthetic toxicity, Oxidative stress, Metabolomics profiling, Apoptotic cell death pathways, Flow cytometry, Mass spectrometry